PERANCANGAN DAN ANALISIS STRUKTUR STATIS PADA MEJA CNC PLASMA CUTTING MENGGUNAKAN SOLIDWORKSPERANCANGAN DAN ANALISIS STRUKTUR STATIS PADA MEJA CNC PLASMA CUTTING MENGGUNAKAN SOLIDWORKS - MUDAKIR, M ROBBY ANGGARA; Malik, Irawan; Anwar Sani, Almadora (Politeknik Negeri Sriwijaya, Indonesia, 2023)
This research was conducted to obtain maximum design results through the QFD (Quality Function Deployment) method as an initial reference that must be considered at the design stage. Conducted to determine consumer needs for products made. Followed by the DFMA (Design For Manufacturing and Assembly) method to get the design results that match the needs and improve the efficiency of the designs made to the time of manufacture and reduce the cost of materials that are not needed. Then at the final stage, a stress analysis simulation is carried out using Solidworks software to determine the maximum stress received due to the given load and can determine the safety of the table frame strength that will be loaded and find out the maximum load that the frame can accept. The material used in the frame is ASTM A36. From the results of this study, it was found that with a given loading of 600 N, the frame experienced a maximum stress of 161.1 Mpa and a yield stress of 257.76 Mpa was obtained and a safety factor of 1.3. So with these data the frame design that has been made is declared safe. And for the maximum load that the frame can accept is 97.88 kg.